Pengaruh Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Kinerja Pegawai Kantor Kecamatan Padalarang Kabupaten Bandung Barat - Ayi Muhiban; Rosmansyah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2022)
The purpose of this research was to find out how much the contribution of the influence of the human resources competency and utilization of information technology on performance of employees of Padalarang District Office, West Bandung Regency. The method of this research is descriptive and associative methods. The analysis unit of this research is 30 employees of Padalarang District Office, West Bandung Regency. The sampling technique in this study is census method. The analysis method used multiple linear regression analysis. The validity and reliability tests were used to test the research instruments. Based on the results of the research, it shows that there is an influence either partially and simultaneously on exogenous variables (human resources competency and utilization of information technology) on endogenous variable (performance of employees). Hopefully this research can make contribution on employees of Padalarang District Office, West Bandung Regency to increase the competencies and maximize the utilization of the information technology so they can increase the performance of employees and the quality of public service.